REDUCTION OF Ni2+ CONCENTRATIONS IN ELECTROPLATING PROCESS WASTEWATER USING CHITOSAN-ACTIVE CARBON ADSORBENT - Az-zahara Adelia; Isni Utami; Caecilia Pujiastuti; Suprihatin; Renova Panjaitan; Anggiany Rizky Kosim (Department of Chemical Engineering, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
The removal of Ni2+ from electroplating process wastewater can be effectively accomplished using chitosan modified with activated carbon through an adsorption process. This research aims to develop adsorbents with varying mass ratios of chitosan to activated carbon and assess their efficacy in reducing Ni2+ concentrations, the impact of contact time on this reduction. Adsorbents were prepared by crosslinking protonated chitosan with tripolyphosphate and incorporating activated carbon in the following ratios: 0.5:1.5, 0.75:1.25, 1:1, 1.25:0.75, and 1.5:0.5 grams per gram. The adsorption process involved contacting 500 milliliters of electroplating process wastewater with 2 grams of adsorbent for various durations of 15 to 75 minutes. Ni2+ concentration in the filtrate was analyzed using Atomic Absorption Spectroscopy (AAS), and the adsorbent was characterized with Scanning Electron Microscopy and Energy Dispersive X-ray Spectroscopy (SEM-EDX). The optimal conditions for Ni2+ removal occurred with a chitosan/activated carbon mass ratio of 0.5:1.5 grams per gram and a contact time of 60 minutes, resulting in a final Ni²⁺ concentration of 2.17 mg/L, an adsorption efficiency of 98.92%, and an adsorption capacity of 49.46 mg/g. These findings demonstrate the effectiveness of chitosan/activated carbon composites in treating Ni2+ contamination in electroplating wastewater, offering a sustainable environmental solution.